Central Corneal Thickness in Females Using Oral Contraceptive Pills - Iqbal, samia; Bashir, Muhammad Khizar; Mateen, Minahal; Amir, Mateen; Ahmad, Iftikhar (Pakistan Journal of Ophthalmology, 2020)
Purpose: To compare the central corneal thickness in females using oral contraceptive pills (OCP) with age matched controls. Study Design: Descriptive Observational study. Place and Duration of Study: Department of ophthalmology, University of Lahore teaching hospital, from August 2018 to December 2018. Material and Methods: Fifty-one females who used OCP within last one year and 38 age-matched controls were included in this study after approval from the ethical review board. Females with any systemic disease, pregnancy and lactating mothers were excluded from the study. Females with ocular diseases, like trachoma, cataract, keratitis, uveitis, corneal dystrophies, Keratoglobus, Keratoconus, ocular trauma, and high refractive errors were also excluded. Each subject underwent full ocular examination including best-corrected visual acuity using Snellen acuity chart and Bio-microscopic examination of anterior segment and the fundus. Central corneal thickness (CCT) was measured with ultrasonic pachymeter and the intraocular pressure was measured with noncontact tonometer at the time of examination. The data was collected by self-designed proforma and analyzed by using SPSS version 20. Results: Mean age of the females using OCP was 31.4 ± 6.8 years and mean age of age-matched controls was 32.9 ± 5.5 years (p = 0.38). Mean Central corneal thickness values were higher in OCP group when compared to controls (541.8 ± 31.39?m and 518.7 ± 36.7 ?m, respectively). P value was 0.004, which was statistically significant. The mean IOP value was 14.5 ± 2.6 mm Hg in OCP group and 14.4 ± 2.8 mm Hg in the control group (P = 0.86), which was not statistically significant. Conclusion: Central corneal thickness values are significantly higher in patients using OCP.